Role of KIT-Positive Interstitial Cells of Cajal in the Urinary Bladder and Possible Therapeutic Target for Overactive Bladder - Yasue Kubota; Yoshiyuki Kojima; Yasuhiro Shibata; Makoto Imura; Shoichi Sasaki; Kenjiro Kohri (Advances in Urology)
In the gastrointestinal tract, interstitial cells of Cajal (ICCs) act as pacemaker cells to generate slow wave activity. Interstitial cells that resemble ICCs in the gastrointestinal tract have been identified by their morphological characteristics in the bladder. KIT is used as an identification marker of ICCs. ICCs in the bladder may be involved in signal transmission between smooth muscle bundles, from efferent nerves to smooth muscles, and from the urothelium to afferent nerves. Recent research has suggested that not only the disturbance of spontaneous contractility caused by altered detrusor ICC signal transduction between nerves and smooth muscle cells but also the disturbance of signal transduction between urothelial cells and sensory nerves via suburothelial ICC may induce overactive bladder (OAB). Recent reports have suggested that KIT is not only a detection marker of these cells, but also may play a crucial role in the control of bladder function. Research into the effect of a c-kit receptor inhibitor, imatinib mesylate, on bladder function implies that KIT-positive ICCs may be therapeutic target cells to reduce bladder overactivity and that the blockage of c-kit receptor may offer a new therapeutic strategy for OAB treatment, although further study will be needed.